Monitoring of methotrexate levels following glucarpidase rescue treatment requires detection by mass spectrometry since immunoassay is not applicable. Issue 2 (12th March 2012) - Zandvliet, M.L.; Jacobs, B.; Boer, E. den; Meesters, R.J.W.; A.l. de, Goede.; Engels, F.K.; de Jonge, R.; Natsch, S.; Koch, B.C.P.
Abstract : Background: Patients treated with high-dose methotrexate may experience severe toxicity when excretion is delayed if acute renal dysfunction develops. Potentially lethal toxicity may be limited by hydration, alkalisation and administration of folinic acid as rescue treatment. In addition, the use of glucarpidase (Voraxaze) may be considered, which is an enzyme capable of degrading methotrexate into glutamate and the metabolite 2, 4-diamino-N10-methylpteroic acid (DAMPA) with very low activity. Glucarpidase is unlicensed in the EU and US, partly due to concerns about pharmaceutical quality, and the interaction with folinic acid, but recent data support its efficacy in reducing methotrexate-induced toxicity. However, limited information is available to support the best dose of glucarpidase if combined with folinic acid. Purpose: In this study, The authors aimed to monitor the effect of glucarpidase administration on methotrexate levels and toxicity in two children with acute renal dysfunction following high-dose methotrexate treatment. Materials and methods: Plasma concentrations of methotrexate were analysed using fluorescence polarisation immunoassay (FPIA) and using two validated matrix-assisted laser desorption ionisation and liquid chromatography mass spectrometry (MALDI/LC-MS) assays. Results: Using FPIA to measure, methotrexate concentrations appeared to remain elevated after glucarpidase administration, and slowly declined thereafter, suggesting a second dose of glucarpidase and high doses of folinic acid. In contrast, MS measurements showed very rapid and nearly complete methotrexate clearance, followed by a minor increase in methotrexate levels, most likely resulting from redistribution. Furthermore, in both children renal function started to recover 24-48 h later, and additional toxicity was minimal. Conclusions: After glucarpidase has been administered, FPIA analysis cannot be used to monitor methotrexate levels, most likely due to cross-reactivity of the metabolite DAMPA. Instead, MS can detect the remaining methotrexate accurately, and confirms nearly complete methotrexate degradation. MS monitoring may result in the prevention of further glucarpidase administration or dialysis, limit the administration of folinic acid, and lead to more rapid discharge from hospital.